Employment, working conditions and mode of living: The case of the Nepali watchmen in Bombay - Paudel, Phanindreshwar (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v2i0.1070 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.59-66